Living with the enemy – German immigrants in Nottingham during the First World War. (2nd January 2017) - Braber, Ben
Abstract: This article uses primary sources to examine German immigrants and their descendants in Nottingham during the First World War. This review is placed in a British context with the aid of secondary sources. It finds that a major provincial city with a relatively very small German population replicated what happened across Britain, but with fear for repercussions contributing to an almost total lack of local support and a failure of the migrants to speak out. It also establishes that the business boycott and exclusion that occurred all over Britain came much later in Nottingham, while anti-German violence was less severe and sustained than elsewhere. In Nottingham well-connected migrants in the lace industry continued to prosper. However, many working and lower middle class migrants were interned and deported or left the city, which resulted in a remarkable decline of the German population of Nottingham.